Electricity generation from biogas: Modern technologies and prospects for Ukraine’s energy independence - O. Sadovoy; D. Koshkin; V. Martynenko; V. Sokolik (Machinery & Energetics, 2025)
Electricity production from biogas and biomethane is a promising area of renewable energy development that can substantially reduce Ukraine’s dependence on fossil fuels, reduce greenhouse gas emissions, and increase energy security. The purpose of the present study was to analyse modern technologies for electricity production from biogas and biomethane, assess their efficiency, technical advantages, disadvantages, and opportunities for integration into the overall energy system of Ukraine. The research methodology included a comparative analysis of cogeneration plants, internal combustion engines, and gas turbines used to generate electricity from biogas, as well as methods of biogas purification to the level of biomethane. The analysis was performed considering technical efficiency, economic feasibility, and environmental safety. The findings of the study revealed that cogeneration units demonstrate the highest efficiency, which ranges from 80-90%, due to the simultaneous production of heat and electricity. Gas turbines provide an efficiency of 30-40%, and internal combustion engines – 25-45%. A comparative analysis of biogas purification methods showed that membrane technologies are the most promising due to their high purification efficiency (95-98%) and economic feasibility. Other methods, such as absorption, cryogenic, and adsorption, have limitations in application due to elevated energy costs or low purification efficiency. It was found that biogas purification to biomethane enables its use for electricity generation, transportation by gas pipelines, and ensuring the stability of power grids, especially during peak load periods. The developed recommendations included improving biogas purification technologies, creating infrastructure for its transportation and storage, and designing mechanisms for government incentives for bioenergy development. The use of bioenergy technologies can ensure the stability of Ukraine’s energy system, increase its efficiency, and reduce dependence on conventional energy sources